2015
DOI: 10.1039/c5ra14446a
|View full text |Cite
|
Sign up to set email alerts
|

Trimethyl-phosphite dissociative adsorption on iron by combined first-principle calculations and XPS experiments

Abstract: The reaction of trimethyl-phosphite, TMPi, with a clean Fe(110) surface has been investigated by ab initio calculations. The most stable configurations and energies are identified for both molecular and dissociative adsorption. The calculated reaction energies indicate that dissociation is energetically more favorable than molecular adsorption and we provide a description of the dissociation path and the associated energy barrier. In situ XPS analysis of adsorbed TMPi on metallic iron confirmed molecular chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
(60 reference statements)
4
37
0
Order By: Relevance
“…The increase of enthalpy is, in fact, ruled by 2 terms, the internal energy and the PV term, and they increase in different ways in TMPi and TBPi, leading to an overall enthalpy increase, which is similar in the two cases. Finally, we observed that the load‐induced dissociation of TMPi proceeds, along the same reaction path as we identified on the open surface in the absence of mechanical stress . The load‐induced dissociation of TBPi proceeds via P─O bond breaking as well.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The increase of enthalpy is, in fact, ruled by 2 terms, the internal energy and the PV term, and they increase in different ways in TMPi and TBPi, leading to an overall enthalpy increase, which is similar in the two cases. Finally, we observed that the load‐induced dissociation of TMPi proceeds, along the same reaction path as we identified on the open surface in the absence of mechanical stress . The load‐induced dissociation of TBPi proceeds via P─O bond breaking as well.…”
Section: Discussionsupporting
confidence: 75%
“…The most favorable adsorption site for the TMPi molecule on the Fe(110) surface has been identified in a previous study by our group by comparing the molecule energies at different symmetry locations on the Fe(110) surface. 29 The configuration shown in Figure 1A, where the P atom of the molecule resides OT of a surface Fe atom, turned out to be the most favorable adsorption geometry. 29 The adsorption of TBPi is simulated by positioning the molecule at the same OT site and performing a structural optimization ( Figure 1B).…”
Section: Molecular Adsorptionmentioning
confidence: 96%
See 3 more Smart Citations